Pengaruh Struktur Modal, Profitabilitas, Likuiditas dan Leverage Terhadap Nilai Perusahaan Studi pada Perusahaan Subsektor Farmasi yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Harfia, Lilik Fasihatul; Pranjoto, R. Gatot Heru (Jurnal Kajian Ilmu Manajemen (JKIM), 2024)
This reìseìarch aims to deìteìrmineì and analyzeì theì influìeìnceì of Capital Struìctuìreì, Profitability, Liquìidity and Leìveìrageì on company valuìeì in pharmaceìuìtical suìb-seìctor companieìs listeìd on theì Indoneìsia Stock Eìxchangeì for theì 2019-2023 peìriod. Theì meìthod uìseìd was a puìrposiveì sampling meìthod and 7 companieìs weìreì obtaineìd. Theì teìchniquìeì uìseìd in this reìseìarch is muìltipleì lineìar reìgreìssion analysis and uìseìs quìantitativeì data. Baseìd on theì reìseìarch reìsuìlts, it shows that: (1) Capital struìctuìreì has a positiveì and significant eìffeìct on company valuìeì (2) Profitability has a positiveì and significant eìffeìct on company valuìeì (3) Liquìidity has a positiveì and significant eìffeìct on company valuìeì (4) Leìveìrageì has a neìgativeì and significant eìffeìct on valuìeì (5) Capital Struìctuìreì, Profitability, Liquìidity and Leìveìrageìsimuìltaneìouìsly influìeìnceì company valuìeì.